Removal Of Color and Chemical Oxygen Demand From Textile Wastewater Using Advanced Oxydation Process (AOPs) - Helmy, Qomarudin; Notodarmojo, Suprihanto; A. Aruan, Indah; Apriliawati, Rizki (IPTEK Journal of Proceedings Series, 2017)
Large quantities of dyes used in the textile industry are lost to the effluents and flows into surface water during the manufacturing and processing operations. Many methods have been used such as biological, physical and chemical treatment of dye containing wastewater. Among these treatment technique, activated sludge, flocculation, and adsorption are the most commonly applied methods in Indonesia. Dyes are usually resistant to aerobic degradation, for example decolorization of azo dyes has been found to be less effective solely using this treatment. On the other hand, flocculation and adsorption methods are not destructive, mainly just concentrate and separate the pollutants phases. This research paper investigates the removal of color and chemical oxygen demand/COD from textile wastewater using advanced oxydation process either by ozone-UV and zinc oxide photocatalyst. Effects of various variables on decolorization and COD removal process have been investigated. The results showed that ozone/UV could achived a complete decolorization (100% removal) when 40 mg/l dye initial concentration was treated with 170.43 ppm/min ozonation for 120 min of incubation period. The same color removal efficiency also achieved when 20 mg/l dye initial concentration treated in the photocatalytic reactor contained 0.71 mg/cm2 of ZnO nanoparticle after 135 min of incubation period. COD removal efficiency for ozone/UV and ZnO photocatalytic treatment was 60% and 77%, respectively.